Digital transformation and its impact on financial management of enterprises operating in industry markets - Khatser, Maxim (Management and Entrepreneurship: Trends of Development, 2025)
The article focuses on developing new scientific solutions for the impact of digital transformation on financial management in Ukrainian enterprises operating in industry markets of different levels (global, international, and national). The scientific and practical necessity of intensifying digital transformation processes in financial management of Ukrainian entities has been described in the context of enhancing the competitiveness of enterprises and their products in industry markets at different levels (global, international, and national). The aim of the article is to identify ways to enhance the efficiency of financial management in Ukrainian enterprises operating in industry markets at different levels (global, international, and national) through the digital transformation of business activities. Methodology: this study employs a combination of general and specialized methods at both empirical and theoretical levels. These include literary analysis to define key terms such as "digital transformation," "digital transformation at enterprises," and "financial management." The abstraction method is used to identify key features of digital transformation in the national economy and enterprises operating in industry markets at different levels (global, international, and national). Induction and deduction methods help determine how digital transformation influences financial management. Analysis and synthesis methods are applied to develop strategies for improving financial management efficiency in Ukrainian enterprises operating in various industry markets. Additionally, systematization, grouping, and logical generalization methods are used to structure information, draw conclusions, and develop scientific proposals. Results: the directions of impact of digital transformation on the efficiency of financial management and the competitiveness of Ukrainian enterprises in industry markets at different levels (global, international, and national) have been identified. JEL Classification: D 21, D 83, L 10, M 10